Recurrent Pregnancy Loss in Obstetrics and Gynecology: An Evidence-Based Framework for Etiologic Evaluation, Risk Stratification, and Patient-Centered Management - Alsaber, Eman; Eman Mansour Alsaber,; Salem Eid Salem Alqhtani,; Abdulaziz Masad Alharbi,; Obaid Fhed Obaid Alenizi,; Fadah Hamad Magaad Albugami,; Mohammed Abdulrahman M Abobaker,; Mohammed Eid S Aljohany,; Mohammed Abdulrashid Abdulkarim Rajab,; Meshari Farzal Ashwi Alshammari,; Reem Fahad Aldosri,; Mariam Mosa Orije, (Saudi Journal of Medicine and Public Health, 2025)
<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Background:<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> Recurrent pregnancy loss (RPL) is a complex and emotionally burdensome condition affecting approximately 2% of pregnant women. It is defined as two or more consecutive pregnancy losses in the U.S. and three or more in the U.K., with up to 50% of cases remaining unexplained despite comprehensive evaluation. <span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Aim:<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> To provide an evidence-based framework for etiologic evaluation, risk stratification, and patient-centered management of RPL. <span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Methods:<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> This review synthesizes current literature on RPL, including epidemiology, pathophysiology, diagnostic strategies, and management approaches. It emphasizes high-yield investigations such as endocrine screening, parental karyotyping, uterine imaging, antiphospholipid antibody testing, and genetic analysis of products of conception. <span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Results:<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> RPL is multifactorial, involving genetic, anatomic, endocrine, immunologic, and lifestyle factors. Established interventions include endocrine optimization, surgical correction of uterine anomalies, and anticoagulation for antiphospholipid syndrome. Emerging therapies such as immunomodulators show limited evidence. Despite structured evaluation, many cases remain unexplained; however, prognosis is generally favorable with supportive care and multidisciplinary management. <span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Conclusion:<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> Effective RPL care requires individualized, evidence-based evaluation, avoidance of low-value testing, and integration of psychosocial support. Multidisciplinary collaboration and patient education are essential to improve outcomes and reduce emotional distress.